Hypocapnia and measurement of airflow resistance and dynamic compliance as functions of respiratory frequency. Issue 3 (March 1982) - Cutillo, A; Bigler, A H; Perondi, R; Turiel, M; Watanabe, S; Renzetti, A D
Abstract : Measurements of lung mechanical behaviour as a function of respiratory frequency may be associated with significantly increased ventilation at high breathing rates. It follows that these measurements may be influenced by hypocapnia which has been shown to increase airflow resistance and to decrease dynamic compliance. To examine this possibility we continuously monitored the end-tidal CO2 tension during the determination of pulmonary resistance and dynamic compliance as functions of frequency and we compared measurements obtained by the standard method and by a technique designed to prevent the development of hypocapnia at high breathing rates. We studied 11 patients with chronic obstructive pulmonary disease and also two smokers with normal spirometry and resistance. Although conventional measurements at frequencies higher than 40-45 breaths/min were associated with a significant decrease in end-tidal CO2, no systematic differences were found between the values of pulmonary resistance and dynamic compliance obtained by the two techniques. Our data indicate that the development of hypocapnia at high breathing rates does not significantly affect measurements of resistance and compliance as functions of frequency, at least when the duration of each period of hyperventilation is limited to the minimum necessary for a single determination, which was less than 30 seconds in the present study. A comparison of our results with previously published data suggests that the time factor may be critical with respect to the possible effects of hypocapnia on these measurements.